1989
DOI: 10.1042/bj2640167
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spermine on mitochondrial Ca2+ transport and the ranges of extramitochondrial Ca2+ to which the matrix Ca2+-sensitive dehydrogenases respond

Abstract: 1. Spermine has previously been reported to be an activator of mitochondrial Ca2+ uptake [Nicchitta & Williamson (1984) J. Biol. Chem. 259, 12978-12983]. This is confirmed in the present studies on rat heart, liver and kidney mitochondria by using the activities of the Ca2+-sensitive intramitochondrial dehydrogenases (pyruvate, NAD+-isocitrate and 2-oxoglutarate dehydrogenases) as probes for matrix Ca2+, and also, for the heart mitochondria, by using entrapped fura-2. 2. As also found previously [Damuni, Humph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Since, however, earlier estimates of mitochondria1 calcium, based on equilibrium thermodynamic considerations, were in the millimolar range, a physiological correlation was not evident. But use of the calcium-sensitive probes, fura-2 or indo-1, made monitoring of the free calcium during changing energy metabolism possible (McCormack, 1989;Wan et al, 1989). These studies were performed on isolated mitochondria and so extrapolation to the in vivo situation is more or less speculative.…”
Section: Influence Of Ca2' On Matrix Granules and Contact Sites Inmentioning
confidence: 97%
See 1 more Smart Citation
“…Since, however, earlier estimates of mitochondria1 calcium, based on equilibrium thermodynamic considerations, were in the millimolar range, a physiological correlation was not evident. But use of the calcium-sensitive probes, fura-2 or indo-1, made monitoring of the free calcium during changing energy metabolism possible (McCormack, 1989;Wan et al, 1989). These studies were performed on isolated mitochondria and so extrapolation to the in vivo situation is more or less speculative.…”
Section: Influence Of Ca2' On Matrix Granules and Contact Sites Inmentioning
confidence: 97%
“…Studies using NMR techniques (Balaban and Heineman, 1989) have demonstrated that the concentrations of these compounds for oxidative phosphorylation do not change appreciably throughout the cardiac cycle and during increases in cardiac work. Hence, the regulation of energy production by calcium ions, present in the mitochondrial matrix, has been studied recently (McCormack, 1989;Wan et al, 1989). Three exclusively intramitochondrial dehydrogenases (e.g., pyruvate dehydrogenase, iso-citrate dehydrogenase, and 2-0x0-glutarate dehydrogenase) are key enzymes for the regulation of oxidative metabolism.…”
Section: Influence Of Ca2' On Matrix Granules and Contact Sites Inmentioning
confidence: 98%
“…Spermine, which increases Ca 2+ uptake by isolated mitochondria from liver (7,8,12,13), brain (8), heart (8,13), and kidney (13), has now been shown to decrease the free-Ca 2+ concentration also in the incubation medium of permeabilized pancreatic islets, presumably through the same mech-anism. Mg 2+ , which antagonizes the effects of spermine on Ca 2+ uptake of mitochondria from different tissues (8), increased the free-Ca 2+ concentration in the incubation medium of permeabilized pancreatic islets.…”
Section: Discussionmentioning
confidence: 97%
“…It has been recognized for many years that precise adjustments in polyamine pools are required for cell growth and differentiation (20). More recent data indicate that the polyamines exhibit substantial antioxidant activity (14,27), regulate certain ion channels and receptors (6,7,17), and modulate a number of mitochondrial functions (21,30). Given the apparent central role of polyamines in regulating cell proliferative and functional states, their importance in governing responses of pulmonary vascular cells in hypoxia seems likely.…”
mentioning
confidence: 99%